Facile Synthesis and Magnetic Behavior of 1d G-C3n4 - Singh, D (Academic Press, 2020)
The graphitic carbon nitride (g-C3N4) material has a unique electronic structure, semiconducting properties, chemical, and thermal stability. These properties make it a suitable candidate for photocatalytic applications. The facile and large scale synthesis of g-C3N4 having new microstructures is always a challenge for its commercial application. A new strategy has been developed to synthesize open-ended Ni encapsulated 1D g-C3N4 nanotubes by using melamine precursor. The g-C3N4 nanotubes synthesized through a new strategy have a length, and diameter of 20 ​μm and ~110 ​nm respectively, with a wall thickness of ~10 ​nm. The magnetic measurements show the low coercive field with a magnetization saturation close to 2 emu/gr at 5 ​K, which may be due to the multi-domain nanoparticle. The magnetization saturation increases with decreasing the temperature. © 2020 Elsevier Inc.